Le sol, une ressource à considérer dans les stratégies d’aménagement des villes : mise en place d’une démarche collaborative pour construire un outil d’aide à la décision d’affectation des sols - Jean-Noël Consalès; Anne Blanchart; Geoffroy Séré; Laure Vidal-Beaudet; Christophe Schwartz (Projets de Paysage)
Although recent projects and landscape architecture designs attempt to address a variety of environmental issues relating to food autonomy, cooling, and water management, it is clear that they still give little consideration to the multifunctionality of urban soils regarding biomass, the water cycle, carbon storage, and biodiversity, and their role in the sustainability of the urban ecosystem. The SUPRA project (Urban soils and development projects : from soil sampling to the creation of a land use decision-making tool - in French, Sols urbains et projets d’aménagement : de l’échantillonnage des sols à l’outil d’aide à la décision d’affectation des sols) is intended to produce new and ground-breaking knowledge to ensure urban planners consider urban soil not only as a substrate but as an element providing potential for urban projects and landscapes in their own right. Within the framework of this programme financed by the French agency for ecological transition, ADEME, the level of knowledge on urban soils and the need for tools were assessed with a wide panel of French territorial and urban planning actors by means of a national online survey and a focus-group workshop. In response to the expectations of the actors surveyed, a decision-making tool was then developed to take into account the potential of soils more effectively in the process of urban planning and landscape projects. This tool, which is currently being calibrated, provides a scoring system for the main soil functions which makes it possible to consider the soil as an essential element in the complexity of the territorial and urban fabric.